Analysis of factors influencing intention to reuse telemedicine applications after the covid-19 pandemic - Manurung, Mona Tiorina; Prameswari, Fanniya Dyah (Institute of Computer Science (IOCS), 2024)
Telemedicine applications in Indonesia have developed rapidly since the COVID-19 pandemic. Telemedicine itself is considered an alternative solution for equal distribution of health services in Indonesia which will continue to grow even after the COVID-19 pandemic is over. However, the use of telemedicine applications is not free from several challenges. Some community groups do not trust the security of patient data and the privacy rights of telemedicine application users. Other community groups also doubt the certification of doctors who provide health consultations or the effectiveness of online examinations. This research wants to find out whether ease of use of the application, trust, and customer satisfaction have a significant effect on the intention to reuse the telemedicine application in the long term. This research uses a descriptive quantitative. The population in this study were users of telemedicine applications in Indonesia. The sampling technique uses a purposive sampling method, namely sampling is carried out by selecting subjects based on specific criteria, namely respondents who have used the telemedicine application at least once and are over 17 years old. The data collection technique used a questionnaire distributed via Googleform to 229 respondents. Data analysis used multiple linear regression analysis and hypothesis testing with SPSS 16 software. The results of this research showed that perceived ease of use, trust, and customer satisfaction had a significant effect on the intention to reuse. The intention to reuse variable is influenced by perceived ease of use, trust, and customer satisfaction by 47.2%.